2012
DOI: 10.1080/00221325.2011.597457
|View full text |Cite
|
Sign up to set email alerts
|

Observing Preschoolers’ Social-Emotional Behavior: Structure, Foundations, and Prediction of Early School Success

Abstract: Social-emotional behavior of 352 3- and 4-year-olds attending private child-care and Head Start programs was observed using the Minnesota Preschool Affect Checklist, Revised (MPAC-R). Goals of the investigation included (a) using MPAC-R data to extract a shortened version, MPAC-R/S, comparing structure, internal consistency, test-retest reliability, and stability of both versions; and, using the shortened measure, to examine (b) age, gender, and risk status differences in social-emotional behaviors; (c) contri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
136
1
7

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 145 publications
(151 citation statements)
references
References 56 publications
7
136
1
7
Order By: Relevance
“…The results indicate that children had a good understanding of what failing to act prosocially meant (Sy et al, 2003). A similar finding resulted from a study conducted by Denham, Bassett, Thayer, Mincic, Sirotkin & Zinsser (2012) used puppets to determine students' ability to identify the emotions of characters. They found that 80% of the students correctly identified the correct emotion that the puppets demonstrated.…”
Section: According To the United States Department Of Health And Humasupporting
confidence: 63%
“…The results indicate that children had a good understanding of what failing to act prosocially meant (Sy et al, 2003). A similar finding resulted from a study conducted by Denham, Bassett, Thayer, Mincic, Sirotkin & Zinsser (2012) used puppets to determine students' ability to identify the emotions of characters. They found that 80% of the students correctly identified the correct emotion that the puppets demonstrated.…”
Section: According To the United States Department Of Health And Humasupporting
confidence: 63%
“…Furthermore, it may be that direct observation actually captures different constructs of social and emotional competence compared to parent and teacher questionnaires that will not otherwise be assessed (Thomas et al, 2011). Last, direct observation may provide a unique benefit to the observer (e.g., teacher, school psychologist, other personnel) by promoting reflection and a unique perspective on the targeted child (Denham et al, 2012;Thomas et al, 2011).…”
Section: Direct Observational Assessmentmentioning
confidence: 95%
“…Therefore, although other direct observation measures may exist, these tools all provide different types of information, and none provides the frequency of both social play behaviors and emotion expressions. For instance, the Individualized Classroom Assessment Scoring System (Downer, Booren, Lima, Luckner, & Pianta, 2010) was developed to rate the overall quality of preschool interactions, the Minnesota Preschool Affect Checklist (Denham et al, 2012;Herndon, Bailey, Shewark, Denham, & Bassett, 2013) indicates the dichotomous presence of target behaviors related to social-emotional functioning, and the Systematic Screening for Behavior Disorders incorporates observation of the frequency of social behavior (Walker & Severson, 1990. These first two systems do not provide information on the frequency of social play behaviors or emotion expressions, instead providing a judgment rating of various social-emotional interactions or skills.…”
Section: Direct Observational Assessmentmentioning
confidence: 99%
See 2 more Smart Citations